Human Herpesvirus 6 and Neuroinflammation. (14th March 2013) - Reynaud, Joséphine M.; Horvat, Branka
Abstract : Human herpesvirus (HHV-) 6A and HHV-6B are two distinct β -herpesviruses which have been associated with various neurological diseases, including encephalitis, meningitis, epilepsy, and multiple sclerosis. Although the reactivation of both viruses is recognized as the cause of some neurological complications in conditions of immunosuppression, their involvement in neuroinflammatory diseases in immunocompetent people is still unclear, and the mechanisms involved have not been completely elucidated. Here, we review the available data providing evidence for the capacity of HHV-6A and -6B to infect the central nervous system and to induce proinflammatory responses by infected cells. We discuss the potential role of both viruses in neuroinflammatory pathologies and the mechanisms which could explain virus-induced neuropathogenesis.